К.РАХМАНОВТЫҢ «ЕДИГЕ» ДРАМАСЫНДА РЕМАРКАЛАРДЫҢ ХЫЗМЕТИ - Палымбетова, М. (FAN va JAMIYAT, 2019)
The article is devoted to the study of remarks used in the musical drama“Edige” by K.Rakhmanov, their role in the description of the heroe’s psychology, profession and actions.